EAU/ESPU guidelines on the management of neurogenic bladder in children and adolescent part I diagnostics and conservative treatment. Issue 1 (13th November 2019) - Stein, Raimund; Bogaert, Guy; Dogan, Hasan S.; Hoen, Lisette; Kocvara, Radim; Nijman, Rien J. M.; Quadackers, Josine S. L. T.; Rawashdeh, Yazan F.; Silay, Mesrur S.; Tekgul, Serdar; Radmayr, Christian
Abstract: Background: In childhood, the most common reason for a neurogenic bladder is related to spinal dysraphism, mostly myelodysplasia. Aims: Herein, we present the EAU/ESPU guidelines in respect to the diagnostics, timetable for investigations and conservative management including clean intermittent catheterization (CIC). Material and Methods: After a systematic literature review covering the period 2000 to 2017, the ESPU/EUAU guideline for neurogenic bladder underwent an update. Results: The EAU/ESPU guideline panel advocates a proactive approach. In newborns with spina bifida, CIC should be started as soon as possible after birth. In those with intrauterine closure of the defect, urodynamic studies are recommended be performed before the patient leaves the hospital. In those with closure after birth urodynamics should be done within the next 3 months. Anticholinergic medication (oxybutynin is the only well‐investigated drug in this age group—dosage 0.2‐0.4 mg/kg weight per day) should be applied, if the urodynamic study confirmed detrusor overactivity. Close follow‐up including ultrasound, bladder diary, urinalysis, and urodynamics are necessary within the first 6 years and after that the time intervals can be prolonged, depending on the individual risk and clinical course. In all other children with the suspicion of a neurogenic bladder due to various reasons as tethered cord, inflammation, tumors, trauma, or other reasons as well as those with anorectal malformations, urodynamics—preferable video‐urodynamics, should be carried out as soon as there is a suspicion of a neurogenic bladder and conservative treatment should be started soon after confirmation of the diagnosis of neurogenic bladder. With conservative treatment the upper urinary tract is preserved in up to 90%, urinary tract infections are common, but not severe, complications of CIC are quite rare and continence can be achieved at adolescence in up to 80% without further treatment. Discussion and Conclusions: The transition into adulthood is a complicated time for both patients, their caregivers and doctors, as the patient wants to become independent from caregivers and treatment compliance is reduced. Also, transition to adult clinics for patients with neurogenic bladders is often not well‐established.